2005
DOI: 10.1055/s-2005-916678
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Monitoring of Primary and Secondary Hemostasis in Coronary Artery Bypass Grafting

Abstract: On-pump cardiac surgery is accompanied by complex alterations of hemostasis. The excessive postoperative bleeding has been attributed to acquired platelet dysfunction, impaired plasmatic coagulation, and increased fibrinolysis. The characterization of the hemostatic defects responsible for bleeding is crucial for specific treatment and optimal clinical management of the patient. For rapid determination of platelet-dependent primary hemostatic capacity (PHC), the Platelet Function Analyzer PFA-100 system is ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
(37 reference statements)
1
32
0
3
Order By: Relevance
“…Recent studies have shown that, compared to conventional coagulation management, TEG/ ROTEM-based POC coagulation management enables reduction of transfusion requirements and costs in cardiac and liver surgery [7,30,33,34,127,128]. Furthermore, TEG/ROTEM may be helpful to identify patients with elevated risk of postoperative thrombotic complications including myocardial infarction [78,129]. However, it must be considered that impaired primary haemostasis because of von Willebrand syndrome or the effect of antiplatelet drugs -like ASA or clopidogrel -cannot be detected by ROTEM analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that, compared to conventional coagulation management, TEG/ ROTEM-based POC coagulation management enables reduction of transfusion requirements and costs in cardiac and liver surgery [7,30,33,34,127,128]. Furthermore, TEG/ROTEM may be helpful to identify patients with elevated risk of postoperative thrombotic complications including myocardial infarction [78,129]. However, it must be considered that impaired primary haemostasis because of von Willebrand syndrome or the effect of antiplatelet drugs -like ASA or clopidogrel -cannot be detected by ROTEM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [119] demonstrated in their study that residual heparin effects can be detected more sensitively by TEG/heparinase-TEG than by activated clotting time (ACT) / heparinase-ACT. Furthermore, the use of heparinase enables monitoring of haemostasis even in completely heparinised patients during cardiopulmonary bypass [78,110,118,120,121]. As the ROTEM system allows measurement at a large temperature range (30-40 °C), the effects of hypo-and hyperthermia on the coagulation system can be verified [22,122].…”
Section: Rotem Parameters and Reference Rangementioning
confidence: 99%
See 1 more Smart Citation
“…The heparin required for anticoagulation during CPB must be reversed by an equivalent dose of protamine [11][12][13]. The interplay of inflammation and coagulation cascades has led many clinicians to argue in favour of a high-dose heparin regimen during conventional CPB [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The viscoelastic changes are recorded and finally converted to a curve. It may help doctors evaluate coagulation fuction to decrease the risk for bleeding and reduce the allogeneic blood transfusion in cardiac surgery with cardiopulmonary bypass and in liver surgery (6,(22)(23)(24). TXA reversibly blocks the lysine binding sites of plasminogen, prevents activation of plasmin and stops lysis of polymerized fibrin.…”
Section: Discussionmentioning
confidence: 99%